First report of Polyxenidae (Diplopoda: Polyxenida) as a host for Charletonia rocciai Treat & Flechtmann, 1979 (Trombidiformes: Erythraeidae) in Brazil - Iniesta, Luiz F. M.; Oliveira, Eli C.; Paranhos, Caroline T.; Bassini-Silva, Ricardo; Bouzan, Rodrigo S.; Jacinavicius, Fernando C. (Entomological Communications, 2024)
Reports of mites parasitizing arthropods are common worldwide. However, there hasn't been a single record of mite parasitism by any Erythraeidae species on the millipede Polyxenidae in Brazil. To address this gap, we present a record of the species Charletonia rocciai Treat & Flechtmann, 1979 (Trombidiformes: Erythraeidae), parasitizing a specimen of this millipede family in the country.